2017
DOI: 10.1038/ajg.2017.196
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Proton Pump Inhibitor Use and Risk of Alzheimer’s Disease

Abstract: In conclusion, we found no clinically meaningful association between PPI use and risk of AD. The results for longer duration of cumulative use or use with higher doses did not indicate dose-response relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 15 publications
3
82
1
Order By: Relevance
“…26 Data from the Finnish nationwide health care registry also reported that among 70,718 newly diagnosed cases of Alzheimer disease, PPI use was not associated with increased risk. 27 Accumulation of amyloid-b peptides is involved in the pathogenesis of Alzheimer disease, and studies have found that lansoprazole led to higher levels of amyloid-b levels in the brains of mice. 28 The PPIs increase amyloid synthesis and decrease amyloid degradation in the brain.…”
Section: Acute and Chronic Kidney Diseasementioning
confidence: 99%
“…26 Data from the Finnish nationwide health care registry also reported that among 70,718 newly diagnosed cases of Alzheimer disease, PPI use was not associated with increased risk. 27 Accumulation of amyloid-b peptides is involved in the pathogenesis of Alzheimer disease, and studies have found that lansoprazole led to higher levels of amyloid-b levels in the brains of mice. 28 The PPIs increase amyloid synthesis and decrease amyloid degradation in the brain.…”
Section: Acute and Chronic Kidney Diseasementioning
confidence: 99%
“…7 To date, the results of epidemiologic studies have also been inconclusive, with more recent studies pointing toward a null association between PPI use and dementia. 8,9 Current knowledge on the relationship between long-term PPI use and cognitive function, a predictor of the risk of dementia in later life, 10 is scant. 11 To investigate the association of long-term PPI use on changes in cognitive function over time, we used prospectively collected data from 2 large cohort studies conducted in Denmark where cognition was repeatedly assessed by trained interviewers, and information on PPI use was ascertained through a nationwide prescription register.…”
mentioning
confidence: 99%
“…Even though the study adjusted for these variables between PPI users and non‐users, additional unrecognized baseline differences (eg, dose and duration of PPI, misdiagnosis of dementia vs delirium, OTC medications or herbal products, family history and genetics) could be present, which might explain the differences in rates of dementia rather than PPI exposure. A Finnish study by Taipale et al compared 70,718 cases of newly diagnosed AD, with up to 4 controls matched for age, sex, and region of residence. With a 3‐year lag window between exposure and outcome, PPI use was not associated with risk of AD (adjusted odds ratio [OR] 1.03; 95% CI, 1.00–1.05).…”
Section: Adverse Effects Of Proton Pump Inhibitorsmentioning
confidence: 99%